Yitzhak Kertesz (1956-1995): In Memoriam - Erenyi, Zvi (Judaica Librarianship, 1995)
The career and contributions of Yitzhak Kertesz, the late Chief Librarian of the Leo Baeck Institute in New York, are described. Appended is a translation of a eulogy by Dr. Jozsef Schweitzer, Director of the Rabbinical Seminary in Budapest, which appeared originally in Hungarian.